Functionalization of Graphene and Applications of the Derivatives - Yang, Guo-hai; Bao, Dan-dan; Liu, Hong; Zhang, Da-qing; Wang, Na; Li, Hai-tao (Journal of inorganic and organometallic polymers and materials, 2017)
Graphene, as one of the most promising new materials, has a wide range of applications in biosensors, super-capacitors and catalysts. Herein, we focus on the covalent and noncovalent modification of both graphene and graphene oxide recently reported, and review the interesting properties, e.g., wider electrical band gap and higher dispersibility. We cover covalent derivatization of graphene and graphene oxide with various species, such as nitrenes, carbenes, aryl intermediates, polymers, biomaterials, carbon materials (fullerenes and carbon nanotubes), and organic molecules. As regards, noncovalent functionalization, we consider π–π interactions, van der Waals forces, ionic interactions, and hydrogen bonding. This review also covers some efforts to achieve tailored functionalization for applications. Finally, we assess the future prospects of covalently and noncovalently modified graphene and graphene oxide (Fig. 1 ).